Amorphous polymerization of nitrogen in compressed cupric azide. Issue 10 (22nd January 2020) - Xu, Yujia; Zhang, Weijing; Zhang, Tonglai; Guo, Wei; Lü, Yongjun
Abstract: Metal azides have attracted increasing attention as precursors for synthesizing polymeric nitrogen. In this article, we report the amorphous polymerization of nitrogen by compressing cupric azide. The ab initio molecular dynamics simulations show that crystalline cupric azide transforms into a disordered network composed of singly bonded nitrogen at a hydrostatic pressure of 40 GPa and room temperature. The transformation manifests the formation of a π delocalization along the disordered Cu‐N network, thus resulting in a semiconductor–metal transition. The estimated heat of formation of the amorphous polymeric nitrogen system is comparable to conventional high‐energy‐density materials. The amorphization provides an alternative route to the polymerization of nitrogen under moderate conditions. Abstract : The amorphous polymerization of nitrogen is realized via compressing cupric azide up to 40 GPa using ab initio molecular dynamics simulations. The amorphous cupric azide features a disordered network bonded by singly‐bonded nitrogen. It is essentially a σ and π mixing bonding net resembling graphene, thus leading to metallization and high energy density. This work theorizes another way of polymerizing nitrogen: amorphization.